Impact of Genes and Proportional Contribution of Parental Genotypes to Inheritance of Root Yield and Sugar Content in Diploid Hybrids of Sugar Beet - Ivica Stancic; Jelica Zivic; Sasa Petrovic; Desimir Knezevic (The Scientific World Journal)
This paper analyzes the impact of genes and proportional contribution of parental genotypes on the inheritance of root yield and sugar content in diploid hybrids of sugar beet. The survey included two diploid male-sterile monogerm lines and three single (SC) male-sterile hybrids as maternal components, while three multigerm diploids were used as pollinators. The partitioning of genotypic variance into additive and dominant components was performed by half sibling (HS) and full sibling (FS) covariance. The proportional contribution of individual components of crossbreeding (lines, testers, and interactions) was exhibited in the expression of certain characteristics of F1 generation. Genotypic variance components showed a significant effect of nonadditive gene action (dominance) in the inheritance of root yield and sugar content, while the additive effect of genes was less significant. Maternal components had a greater proportional contribution to root yield, while lines, pollinators, and their interactions had an equal contribution to sugar content.